Bidhan Sadabahar: A bushy cowpea variety resistant to cowpea aphid borne mosaic virus - Chattopadhyay, Arup; Dutta, Subrata; Mandal, Asit Kumar; Maurya, Praveen Kumar; Banerjee, Swadesh; Bhattacharjee, Tridip; Hazra, Pranab (Indian Horticulture, 2020)
Bidhan Sadabahar, a bushy, early maturing, high yielding variety, having resistance to cowpea aphid borne mosaic (CABM) virus (both under field and sap transmission), and field resistance to pod borer, has been developed through hybridization followed by selection from a cross between Bidhan Barbati 1 and Kashi Kanchan by Bidhan Chandra Krishi Viswavidyalaya, Mohanpur, Nadia, West Bengal. This variety has been released by the State Variety Release Committee, West Bengal and notified by the Central Variety Release Committee for State release during 2019. Pods are pulpy, meaty and soft with less fibre. The variety can be fitted well in multiple cropping system, and can perform well in eastern parts of India apart from West Bengal.